Functional Outcomes of Schatzker Type III–VI Tibial PlateauFractures Treated with Anatomical Locking Compression Plates:An Observational Study - Yadav, Sumit; Thapa, Bikash; Onta, Pratyentaraj; Tiwari, Ganesh (Medical Journal of Armed Police Force Nepal, 2026)
Introduction: Tibial plateau fractures, frequently caused by road traffic accidents, disrupt articular congruity and elevate the risk of secondary osteoarthritis. Although anatomical locking compression plates are widely used for fixation, outcomes for Schatzker III-VI fractures remain underexplored. This study evaluated the functional and radiological outcomes of Schatzker type III-VI fractures treated with locking compression plates. Methods: In this observational study, 30 patients with Schatzker III-VI fractures underwent locking compression plates fixation at a single center between November 2021 and December 2022. Ethical clearance was obtained from the Institutional Review Committee (15 August 2021). Functional outcomes were assessed using the Knee Society Score at a minimum 4-month follow-up. Radiographic union was evaluated on standard anteroposterior and lateral radiographs, defined as bridging callus across at least three of four cortices on two orthogonal views with no visible fracture line. Data were analyzed descriptively, continuous variables were expressed as mean ± standard deviation, and categorical variables as frequencies and percentages. Results: The mean patient age was 44.50±14.38 years, with road traffic accidents being the predominant injury mechanism. At the 4-month follow-up, the mean Knee Society Score was 75.33±7.53. Good outcomes were observed in 21 (70%) of patients and excellent outcomes in 5 (16.70%). Fair and poor outcomes were each observed in 2 (6.70%) of cases. Radiographic union was evident in 28 (93.30%) of fractures. Complications included superficial infection 6 (20%) and knee stiffness 4 (13.30%). Conclusions: In patients with Schatzker type III-VI fractures, treatment with locking compression plates achieved high rate of good-to-excellent functional outcomes and fracture union at 4 months, supporting its role as an effective surgical strategy for these injuries.